2019
DOI: 10.1002/anie.201910993
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropically Electrochemical–Mechanical Evolution in Solid‐State Batteries and Interfacial Tailored Strategy

Abstract: All‐solid‐state batteries have attracted attention owing to the potential high energy density and safety; however, little success has been made on practical applications of solid‐state batteries, which is largely attributed to the solid–solid interface issues. A fundamental elucidation of electrode–electrolyte interface behaviors is of crucial significance but has proven difficult. The interfacial resistance and capacity fading issues in a solid‐state battery were probed, revealing a heterogeneous phase transi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 44 publications
0
36
0
Order By: Relevance
“…[ 75 ] For FeS 2 with a huge volume variation of 159.20%, the expansion during initial discharging process together with heterogeneous conversion reaction from different orientations provoked the observed separation from the ionic conducting network. [ 76 ] A similar but severer crack was observed for the electrode composing of S anchored on reduced graphene oxide and Li 10 GeP 2 S 12 after 750 cycles at 1 C (Figure 6f), which was eventually pulverized into powders. [ 77 ]…”
Section: Issues For the Cathode Encountering Solid Electrolytementioning
confidence: 57%
“…[ 75 ] For FeS 2 with a huge volume variation of 159.20%, the expansion during initial discharging process together with heterogeneous conversion reaction from different orientations provoked the observed separation from the ionic conducting network. [ 76 ] A similar but severer crack was observed for the electrode composing of S anchored on reduced graphene oxide and Li 10 GeP 2 S 12 after 750 cycles at 1 C (Figure 6f), which was eventually pulverized into powders. [ 77 ]…”
Section: Issues For the Cathode Encountering Solid Electrolytementioning
confidence: 57%
“…were able to follow the propagation of the reaction front by tuning to the Fe–K edge. [ 329 ] Notably, a very heterogeneous FeS 2 ‐core Fe‐shell structure was found for the final discharged state, which is considered as one of the many factors causing the observed capacity decay. Besli et al.…”
Section: Interface‐sensitive Techniquesmentioning
confidence: 99%
“…141 Despite the noticeable formation and growing of an interphase layer between the electrodes and the solid electrolyte, it was shown that the formation, propagation and widening of microcracks was responsible for the failure of the cell. The evolution during cycling of the microstructure of composite electrodes has also been successfully probed by in situ and operando X-CT. 142,143 An interesting example has been published by Yuta Kimura and coworkers. They combined synchrotron X-CT and X-ray absorption near edge structure (XANES) spectroscopy to evaluate operando the 3D spatial distribution of the state of (dis)charge (SOC) of LCO particles in a composite electrodes containing Li2.2C0.8B0.2O3 (LCBO) as solid electrolyte without the presence of conductive additives.…”
Section: X-ray Computed Tomography (X-ct)mentioning
confidence: 99%